Sumber Gagasan Penciptaan Karya Audio Visual Berbasis Konten Lokal - Sintowoko, Dyah Ayu Wiwid (Seni Media Rekam ISI Surakarta, 2014)
Creativity can be done by utilizing the environment, natural resources, and human resources. Human Resorces can attempt to pour out their thoughts, find problems, and take chances, and viable solutions to publish. Creativity through the media can inspire, encourage, influence, and able to bring a positive change for the audience. The potential of these natural resources that need to be developed by the community at the same time revive, that the stored wealth needs to be raised (one of them with audio-visual approach). In this case the community (residents) as actors, not only as a spectator only. Their awareness that we must lift to play the audio-visual media. Something extraordinary in rural or are citizens can see themselves, relatives, family, and neighbors through the medium of film and television, so that it becomes an individual and collective pride.